Morphological, physical and chemical characterization of the soils of North Kuttanad - Manorama Thampatti K C (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1997)
An investigation was carried out at the College of Horticulture, Vellanikkara during 1992 to 1995 to evaluate the morphological, physical and chemical characteristics of soils of North Kuttanad and to assess the extent of toxic factors that pertained in the soil due to restricted movement of water under the influ- ence of Thanneermukkom regulator. The study was carried out in three parts, viz., (1) Morpho- logy and physicochemical characteristics, (2) Fertility characteristics and (3) Toxicity chara- cteristics. Fifteen soil profile were drawn from North Kuttanad to study the morphology and physicochemical characteristics of the area. The fertility characteristics were studied by collecting 97 surface soil samples (0-15 cm depth) from 27 padasekharams of the area during rainy and summer seasons (before and after the closure of Thanneermukkom regula- tor). Toxicity characteristics of the area were studied by collecting bulk soil samples (0-25 cm depth), surface water and ground water from the above sites during the same period. Morphological and physicochemical properties of the soils showed great degree of variation. Soils were dark brown to black in colour, sticky and plastic, subangular blocky in structure and sandy to clayey in texture, with random deposits of lime shells and humus. Presence of faint to prominent reddish yellow or brown mottles, rice roots and root canals were some of the special characteristics observed in the soil profiles. Soils of the area were highly acidic and mildly saline. Both soil acidity and salinity increased with depth. Organic carbon, CEC and ECEC of the area were higher compared to other parts of Kerala, but the base saturation was comparatively lower. The area was rich in almost all the essential nutrients except P. Fe, Al and S were present in toxic concentrations.